Use of fluoridated dentifrices by children in Araçatuba, Brazil: factors affecting brushing habits and amount applied on the brush - Coclete, G. E.G. [UNESP]; Delbem, A. C.B. [UNESP]; Sampaio, C. [UNESP]; Danelon, M. [UNESP]; Monteiro, D. R. [UNESP]; Pessan, J. P. [UNESP] (Springer Nature, 2021)
Purpose: To evaluate the type and the amount of fluoridated dentifrice applied on children’s toothbrushes by parents/guardians according to descriptions typically recommended by scientific societies, as well as to assess the influence of demographic and socioeconomic variables on dentifrice use. Methods: Parents/guardians of children (0–7 years old; n = 306; convenience sample) attending vaccination centres from Araçatuba (Brazil), answered to a structured questionnaire comprising items related to interviewees’ education, child’s age, gender, brushing habits and use of fluoridated dentifrice. The amount of toothpaste used by children during toothbrushing was estimated using a portable scale. Similarly, the interviewees were requested to apply dentifrices on toothbrushes according to eight descriptions, ranging from “smear” to “all bristles”, following a random sequence. Data were submitted to Mann–Whitney’s, Kruskal–Wallis’ and Friedman’s tests, and Spearman’s correlation coefficient (p < 0.05). Results: The type of toothpaste and the amount of product used at home were not affected by the respondents’ educational level or family income. However, child’s age was significantly correlated with the amount of toothpaste placed on the toothbrush (r = 0.324, p < 0.001). Also, the amount of toothpaste placed on the toothbrush increased according to what would be expected from the descriptions, although wide variations were observed within each description, with large interquartile and overall ranges. Conclusion: The amount and the type of dentifrice used by children were influenced by their age, while parents/caregivers’ interpretation on verbal instructions regarding appropriate dentifrice quantities varied widely. This reinforces the need for educative measures on the appropriate use by dentifrices by children.
Keywords: Child; Dental; Dental caries; Fluorides; Fluorosis; Toothpastes